Arthroscopic fixation techniques for tibial eminence fractures in pediatric patients: a review - Li, Canfeng; Huang, Xiancheng; Yang, Qingjun; Luo, Yong; Li, Jiatong; Ye, Sufen; Lu, Wenqian; Zhang, Xintao; You, Tian (Frontiers in Pediatrics, 2024)
The introduction of new internal fixation devices and arthroscopic techniques has led to significant changes in the surgical treatment of tibial eminence fractures (TEFs) in children. In recent years, arthroscopic surgery has arisen as the gold standard for the treatment of TEFs. This popularity of arthroscopic techniques has reduced surgical complications and improved patient prognosis. In this paper, we investigate the current situation of the use of arthroscopic fixation techniques for pediatric TEFs. We searched the PubMed database using the terms “arthroscopic treatment and tibial eminence,” “arthroscopic treatment and tibial spine,” “tibial eminence avulsion”, “tibial spine fracture”, with no limit on the year of publication. From these articles, we reviewed the use of various arthroscopic TEFs fixation techniques reported in the current literature. Overall, we found that the choice of fixation method seems to have no effect on clinical outcomes or imaging results. However, if an easy, strong fixation that is less prone to epiphyseal damage is desired, as a junior practitioner, the anchor technique should be mastered first, whereas for senior practitioners, a variety of fixation techniques for TEFs should be mastered, including anchors, sutures, and screws, so that personalized fixation can be achieved with the least amount of trauma, operative time, and complications. Higher quality studies are needed in the future to provide Useful evidence to determine the optimal fixation technique in terms of clinical outcomes, function, and complications.